Provider satisfaction with the health information system based on the electronic health records in Burundi’s hospitals - Munezero, Florence; Sossa, Charles J.; Nyandwi, Joseph; Bazira, Leodegal (International Journal Of Community Medicine And Public Health, 2022)
Background: The computerization of the health record is one of the means to improve the performance of the information system within the hospital and therefore improve the continuity and quality of care and services offered to the population. The objective of this work was to determine the factors associated with the satisfaction of providers with the hospital information system based on the electronic health record. Methods: This is a cross-sectional, descriptive and analytical study carried out in 11 hospitals in Burundi. A self-administered questionnaire was used to collect data from a sample of 155 providers. The data analysis was done with STATA 15. Results: The majority were nurses (51%) followed by physicians (23%). Regarding satisfaction, 55.5% of the providers were satisfied with the new EHR-based system. Men were 2.21 times more satisfied with the use of the EHR than women (OR=2.21; CI95%: [1.09-4.46]). Providers who were trained by the project’s computer scientists were 4.24 more satisfied than those who were trained by their colleagues (OR=4.24; CI95%: [1.47-12.23]) and 3.69 more satisfied than those who were trained by the hospital’s computer scientists (OR = 3.69; CI95%: [1.25-10.89]). Similarly, the use of the software to generate reports and statistics was 2.27 times associated with provider satisfaction (OR=2.27; 95% CI: [1.14-4.49]. Conclusions: The sustainability and success of the patient record computerization project depends on taking into account the expectations of the providers during the implementation.